The Effect of Web-Based Education Media Toward Balanced Nutritional Eating Behavior on High School Students in Surabaya - Shofia Lathifa (Universitas Airlangga, 2020)
Changes towards unhealthy eating patterns in the long run will result on nutritional problems. This change is partly due to technology advancement that make it easy for people to be exposed by food advertisements and unhealthy diets practices. It also makes people easier to instantly getting food that they crave. Technological developments, on the other hand, can be used as an educational medium to prevent nutritional problems, one of which is through a media website (web). This study aims to look at the influence of web-based educational media on balanced nutrition behavior of high school students in Surabaya. This research was an experimental quasi research with a pretest posttest control group design conducted on 38 high school grade X students in Surabaya, East Java. The intervention was conducted at Surabaya's Khadijah High School using web-based nutrition education media and 17 August 1945 Surabaya High School using leaflets. Changes in balanced nutritional eating behavior before and after the intervention were measured using a validated questionnaire. Based on the results, there were 66.7% of students with good levels of knowledge, 61.9% of students with positive attitudes, and 61.1% of students with good balanced nutrition practices in the leaflet group. Meanwhile, in the web group, there were 55.6% of students with good knowledge levels, 55.6% of students with positive attitudes, and 50% of students with good balanced nutrition practices. After the intervention, in the leaflet group, the number of students with good knowledge, positive attitudes, and good balanced nutrition practices increased to 72.2%, 83.3% and 77.8%. Whereas in the web group, the number of students with good knowledge, positive attitudes, and good balanced nutrition practices increased to 100%, 88.9% and 94.4%.